ANALYSIS OF THE SHORT STORY “THE SELFISH GIANT” BY OSCAR WILDE USES AN OBJECTIVE APPROACH - Padilatul Hasanah (Cahaya Ilmu Bangsa Institute, 2024)
This research is to analyze the intrinsic elements in the short story “The Selfish Giant” using an objective appoarch.The research method that I use in this analysis uses a qualitative descriptive method,which is a thorough and in-depth research.This short story is highly recommended to be read by all people because there is an educational element in the short story,and there are many messages and impression in the short story.This plot is very understanable because itdoesn’t make the reader dizzy.